2020
DOI: 10.1080/10942912.2020.1807567
|View full text |Cite
|
Sign up to set email alerts
|

Saffron supplementation effects on glycemic indices: a systematic review and meta-analysis of randomized controlled clinical trials

Abstract: Existing evidence on the possible effects of saffron on glycemic indices were inconclusive. The aim of the present systematic review and meta-analysis was to clarify the effects of saffron supplementation on glycemic indices, including fasting blood glucose (FBG), fasting insulin, glycated hemoglobin (HbA1c), Quantitative Insulin Sensitivity Check Index (QUICKI) and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) among both diabetic and nondiabetic patients. A systematic literature search of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 35 publications
(97 reference statements)
0
36
0
Order By: Relevance
“…The activation of AMPK promotes GLUT4, which leads to the improvement of insulin-stimulated glucose uptake. 51 Physical activity is considered a beneficial strategy with antiinflammatory properties, which reduces the risk of inflammatoryrelated diseases. 1 The concomitant integration of RT and AT within a periodized training program is termed 'concurrent training' or circuit training.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AMPK promotes GLUT4, which leads to the improvement of insulin-stimulated glucose uptake. 51 Physical activity is considered a beneficial strategy with antiinflammatory properties, which reduces the risk of inflammatoryrelated diseases. 1 The concomitant integration of RT and AT within a periodized training program is termed 'concurrent training' or circuit training.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double blind, placebo-controlled study, supplementation of saffron tablets in 40 type-2 diabetic patients vs. 40 control subjects for 12 weeks, reduced waist circumference and malondialdehyde levels, although no changes were noted in blood glucose levels, lipid profiles, C-reactive protein, and pro-inflammatory marker tumor necrosis factor [ 135 ]. However, in a systematic and meta-analysis study of 15 randomized controlled trials involving 1139 subjects, saffron was shown to decrease glycemic indices including FBS, HbA1c, and fasting insulin, and increased quantitative insulin sensitivity check index [ 136 ].…”
Section: Herbal Approaches To Management In Metabolic Syndromementioning
confidence: 99%
“…It is a commonly consumed spice for flavoring, aromatizing, and coloring food in different parts of the world (Ghaffari & Roshanravan, 2019;Kang et al, 2012). The beneficial effects of saffron can be attributed to a number of components in its stigmas, including crocetin (a carotenoid derivative), crocin (a 20-carbon diglycosidic ester of crocetin), picrocrocin (a colorless glycoside responsible for the bitter taste of saffron), safranal (a volatile oil responsible for the saffron aroma), anthocyanins, and flavonoids (Bathaie & Mousavi, 2010;Sohaei et al, 2020). Besides these components, amino acids, proteins, starch, vitamins (such as riboflavin and thiamine), minerals, and gums are other chemical compounds of saffron (Bathaie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%